2010
DOI: 10.1016/j.jcrs.2009.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Ocular blood-flow hemodynamics before and after application of a laser in situ keratomileusis ring

Abstract: In normal healthy eyes, once suction was released, blood-flow responses returned immediately to normal levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…This could be a result of IOP increased beyond perfusion pressure. As a result, ocular blood flow might be reduced below a critical level, 17,18 or possibly direct transient stress to the optic nerve fibers in the lamina cribrosa might cause the sensations reported by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a result of IOP increased beyond perfusion pressure. As a result, ocular blood flow might be reduced below a critical level, 17,18 or possibly direct transient stress to the optic nerve fibers in the lamina cribrosa might cause the sensations reported by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in the slope of the regression line (becoming more negative) with increasing ODF as seen in Figs 7 and 8 and the negative values in the interaction terms in Eqs 13 and 14 involve complex hemodynamic mechanisms, which are poorly understood. Theoretical [91] and experimental models [92][93][94] have attempted to investigate the retinal and retrobulbar hemodynamic changes from induced IOP elevation. Harris et al using color doppler imaging, reported changes in the central retinal artery (CRA) including reduced peak systolic velocity, end-diastolic velocity and an increase in the resistive index.…”
Section: Plos Onementioning
confidence: 99%
“…One hypothesis is that application of a microkeratome induces IOP increases up to 90 mm Hg and changes the shape of the eye. [24][25][26][27] The anterior segment is drawn into a vacuum chamber, and the eye elongates along the anteroposterior axis. Because the globe is a closed system, the eye must contract along the horizontal axis.…”
Section: Discussionmentioning
confidence: 99%